ENKAPSULASI KETOPROFEN DENGAN KITOSAN-ALGINAT BERDASARKAN JENIS DAN RAGAM KONSENTRASI TWEEN 80 DAN SPAN 80 - Sugita, Purwantiningsih; Napthaleni, Napthaleni; Kurniati, Mersi; Wukirsari, Tuti (Makara Journal of Science, 2010)
Encapsulated Ketoprofen by Chitosan-Alginat based on Type and Variation of Tween 80 and Span 80 Concentration. Ketoprofen has been encapsulated by chitosan-alginate based on types of surfactant and it’s concentration. The variations of concentration either Tween 80 (polietilena sorbitanmonooleat) or Span 80 (sorbitanmonooleat) that used were around (1- 3)% concentrations with stirring around (15-60) minutes. The using of Tween 80 resulted efficiency of encapsulated ketoprofen and nano particle size (100-1000) nm are higher than Span 80.